1994
DOI: 10.1177/0148607194018005453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Closed” vs “Open” Systems for the Delivery of Peptide‐Based Enteral Diets

Abstract: Nonvented closed-delivery containers may be safely infused for up to 48 hours. They are associated with reduced labor and contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 16 publications
0
16
0
3
Order By: Relevance
“…64,65 Different administration sets have been evaluated for risk of inadvertent contamination in the process of filling the container. 43,66 The authors concluded that the adherence to strict aseptic technique is the key to prevention of contamination during the filling process.…”
Section: Reducing Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Different administration sets have been evaluated for risk of inadvertent contamination in the process of filling the container. 43,66 The authors concluded that the adherence to strict aseptic technique is the key to prevention of contamination during the filling process.…”
Section: Reducing Contaminationmentioning
confidence: 99%
“…63 A recent Spanish article reports a randomized trial of immediate feeding in over 30 patients with no increase in complications. 64 In the pediatric literature, the shortest time course to using a PEG was described in a clinical report by Werlin et al 65 This study was uncontrolled, but the authors reported no unusual complications that led to feeding discontinuation in 24 pediatric patients started on Pedialyte ® (Abbott Laboratories) 6 hours after PEG placement. …”
mentioning
confidence: 98%
“…7). This level, 10 4 cfu ml -1 , has been quoted as a critical value above which feed is unacceptable for patient consumption (Fagerman 1992, Wagner et al 1994, Food and Drug Administration 1995. However, 10 4 cfu has also been reported as the number of organisms required for gut colonization (Pottecher et al, 1979) and it has been stated that consumption of 1 g of food containing 10 3 Gram negative bacilli can lead to persistent gut colonization in patients receiving systemic doses of antimicrobial agents (Remington and Schimpff 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The most likely vehicle was believed to be the hands of staff (Schreiner et al 1979 ). Epidemiological and microbiological links between enteral nutrition and feeding intolerance, abdominal distention, aspiration pneumonia, diarrhoea, necrotizing enterocolitis, and even systemic infections such as sepsis caused by bacterial contamination have been reported (Anderson et al 1984 ;Anderton 1993 ;Freedland et al 1989 ;Wagner et al 1994 ).…”
Section: Biofi Lms On Enteral Feeding Tubes and Antimicrobial Resistancementioning
confidence: 99%
“…Feeding procedures and practices such as the Hazard Analysis Critical Control Point system (Bryan 1990 ) need to be monitored (Anderton 1995 ). The closed ready-to hang enteral nutrition delivery system is believed to be an effective method for contamination-free enteral feeding (Chan et al 1994 ;Curtas et al 1991 ;Wagner et al 1994 ).…”
Section: Prevention Of Neonatal Infections Caused Be Contaminated Entmentioning
confidence: 99%